A QUANTITATIVE STUDY INVESTIGATING SOCIOECONOMIC INEQUALITIES IN HIGHER EDUCATION: BARRIERS TO ACCESS AND SUCCESS AT MANGOSUTHU UNIVERSITY OF TECHNOLOGY (MUT). - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Access to higher education in South Africa remains a challenge for students from socioeconomically disadvantaged backgrounds. Despite progressive policies aimed at widening participation, many students face financial constraints, limited academic preparation, and insufficient institutional support. Mangosuthu University of Technology (MUT), a historically disadvantaged institution, provides a relevant context to investigate these barriers. Methods A quantitative study was conducted with 300 participants: 250 undergraduate students, 30 faculty members, and 20 policymakers. Data were collected using structured questionnaires and institutional records. Participants were diverse in age (ranging from 18 to 26 years for students), gender (58% female, 42% male), and residential background, with 64% of students coming from rural areas. Descriptive and inferential statistics were applied to identify patterns linking socio-demographic variables to educational access and success. Results The findings reveal that 80% of students from low-income households struggled to afford tuition, accommodation, and learning materials. Approximately 75% reported inadequate access to academic resources, including the internet and textbooks. In addition, 65% of students whose parents had not pursued higher education indicated poor academic preparedness and difficulty adjusting to university demands. Students from rural backgrounds reported challenges in transitioning to university life and accessing support services. Financial aid was available, but delays and complex procedures were commonly reported. Conclusion Socioeconomic and demographic disparities remain a major barrier to equitable access and academic success at MUT. Financial difficulties, insufficient academic support, and systemic challenges disproportionately affect students from rural and low-income households. Recommendations The study recommends strengthening financial aid systems, improving access to academic resources, and introducing targeted transition programs for first-generation and rural students. These strategies are essential to foster inclusive participation and support student success in higher education.